Inpatient Readmission Insidence of National Health Insurance Patients at Partner Hospitals of BPJS-Health in Sukabumi 2015 - Atmiroseva, Atmiroseva; Nurwahyuni, Atik (UI Scholars Hub, 2017)
The INA-CBG payment system in the JKN program allegedly increasing the incidence of readmission. This study aims to map the incidence of readmission in JKN participants admitted to thirteen partner hospitals of BPJS-Health in Sukabumi. The research design is a descriptive study with the unit of analysis is patient. The study used secondary data from inpatient claims in thirteen partner hospitals BPJS-Health Sukabumi which has been verified during 2015. The study found that the number of readmission is 8.81% with the most readmission incidence occurs in the equal CMG category and at the least in the equal severity level category. The cost of inpatient readmission services is more expensive 104-113% of the initial care cost. Moreover, about 15- 16% cases of severity level readmission is increasing and 12-13% of its severity level is decreased. Less than 3% cases of readmission ended not good because they died, were referred, or had to come home forcibly.